THE INFLUENCE OF MONETARY POLICY ON CORPORATE FINANCIAL PLANNING IN INDONESIA - Ardelia Suharmanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Monetary policy plays an important role in a country's economy, including in corporate financial planning. This study aims to analyze the effect of monetary policy, as measured by instruments such as interest rates, inflation, and money supply, on corporate financial strategies in Indonesia. The research method used is a quantitative approach with secondary data analysis from corporate financial reports and macroeconomic indicators issued by Bank Indonesia. The results of the study indicate that changes in interest rates and inflation rates have a significant impact on investment decisions, capital structure, and corporate liquidity management. Monetary policy uncertainty can also increase the financial risks faced by companies in the long term. The implications of these findings indicate the importance of adapting corporate financial strategies to the dynamics of monetary policy in order to ensure sustainable business stability and growth.